The Effects of the COVID-19 Pandemic on Maine’s Labor Market and Workforce - McInerney, Mark; Fenton, Erin (Maine Policy Review, 2021)
This article uses a variety of data sources to examine the pandemic’s impact on the labor market in Maine, first by putting it in the context of past recessions, then by assessing telework suitability across occupations, and finally by exploring the differential job losses that occurred during the pandemic by sector and by gender and educational attainment.
Keywords: recessions; telework; job loss; job recovery; unemployment